Distribution of uranium, thorium and some stable trace and toxic elements in human hair and nails in Niška Banja Town, a high natural background radiation area of Serbia (Balkan Region, South-East Europe). (July 2015) - Sahoo, S.K.; Žunić, Z.S.; Kritsananuwat, R.; Zagrodzki, P.; Bossew, P.; Veselinovic, N.; Mishra, S.; Yonehara, H.; Tokonami, S.
Abstract: Human hair and nails can be considered as bio-indicators of the public exposure to certain natural radionuclides and other toxic metals over a long period of months or even years. The level of elements in hair and nails usually reflect their levels in other tissues of body. Niška Banja, a spa town located in southern Serbia, with locally high natural background radiation was selected for the study. To assess public exposure to the trace elements, hair and nail samples were collected and analyzed. The concentrations of uranium, thorium and some trace and toxic elements (Mn, Ni, Cu, Sr, Cd, and Cs) were determined using inductively coupled plasma mass spectrometry (ICP-MS). U and Th concentrations in hair varied from 0.0002 to 0.0771 μg/g and from 0.0002 to 0.0276 μg/g, respectively. The concentrations in nails varied from 0.0025 to 0.0447 μg/g and from 0.0023 to 0.0564 μg/g for U and Th, respectively. We found significant correlations between some elements in hair and nails. Also indications of spatial clustering of high values could be found. However, this phenomenon as well as the large variations in concentrations of heavy metals in hair and nail could not be explained. As hypotheses, we propose possible exposure pathways which may explain the findings, but the current data does not allow testing them. Highlights: Niška Banja is a high radiation background area of Serbia with high radium ( 226 Ra) concentration. Measurement of thorium, uranium and some selected trace elements in hair and nails were carried out using ICP-MS. Elevated concentration of naturally occurring radionuclides such as U and Th in environmental samples was determined. We have assumed to find a suitable relationship between hair and nail samples with the natural samples.